Fundamentals of dimensional metrology - Busch, Ted.; Harlow, Roger; Thompson, Richard (Albany, NY : Delmar, 1998)
This book is about: Measurement and metrology; Measurement, Gaging, and tolerances; Statistics and metrology; Language and systems of measurement; Vernier instruments; ...
Keywords: Mensuration; Mensuration; Measuring instruments